Using halotolerant Azotobacter chroococcum W4ii from technosoils to mitigate wheat salt stress [version 3; peer review: 2 approved, 1 not approved] - Sweta Binod Kumar; Agnieszka Kalwasińska; Monika Wróbel; Maria Swiontek Brzezinska (Open Research Europe, 2024)
Background Technosoils in Inowrocław, central Poland, are impacted by human activities and exhibit high salinity (ECe up to 70 dS/m) due to a soda lime repository. These saline environments pose challenges to plant growth and soil health. However, they also offer an opportunity for the evolution of microorganisms adapted to such conditions, including plant growth-promoting rhizospheric (PGPR) bacteria. The hypothesis tested here was that introducing PGPR bacteria from these environments could boost degraded soil performance, leading to better plant biomass and improved pathogen defense. Methods Azotobacter chroococcum W4ii was isolated from the rhizosphere of wheat (Triticum aestivum L.) for its plant growth properties on wheat plants under salt stress. Results Wheat seeds co-inoculated with A. chroococcum W4ii under 200 mM salt stress showed significant improvement in various growth parameters such as seeds germination (by 130%), shoot biomass (15%), chlorophyll b content (40%) compared to un-inoculated ones. Bacterial inoculation decreased the level of malondialdehyde (MDA), whereas it elevated the antioxidative enzymatic activities of peroxidase (POD). The test isolate also enhanced the level of defense enzymes like β-1,3-glucanase, which can protect plants from infection by pathogens. The bacterium could also successfully colonize the wheat plants. Conclusions These results indicate that A. chroococcum isolated from the technosoil has the potential to promote wheat growth under salt stress and can be further used as a bioinoculant in the salt affected agricultural fields.